HUBUNGAN KECEMASAN TERHADAP KUALITAS TIDUR MAHASISWA BARU PRODI FISIOTERAPI UNIVERSITAS BALI INTERNASIONAL - I Gusti Ayu Sri Wahyuni Novianti; Ida Ayu Astiti Suadnyana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The problem that occurs in new students is anxiety. This anxiety can be caused by changes in the social environment. This change in situation causes uncertainty which will lead to increased secretion of adrenaline. Academic problems such as study load can be another factor for students experiencing anxiety. When someone feels anxious, there will be an increase in the hormones cortisol, epinephrine, and norepinephrine which is affect the central nervous system, causing a state of wakefulness and increasing alertness in the central nervous system. This will make it difficult for students to start sleeping and cause poor sleep quality. This study aims to determine the relationship between anxiety and sleep quality in the new students in Prodi Fisioterapi Universitas Bali Internasional. This study used a cross sectional study design. The sampling technique used is the total sampling for 29 people. The research was conducted at the Program Studi Fisioterapi Universitas Bali Internasional in December 2021. Measurement of sleep quality using PSQI (Pittsburgh Sleep Quality Index) and anxiety measured using HSR-A (Hemiilton Rating Scale for Anxiety). Data  were analyzed with SPSS 23.0, using the  chi  square  test. The results between anxiety and sleep quality is p=0,001 (p<0,05), which means  that there  is  a  significant relationship between anxiety and sleep quality in new students.